Brief Report: Measurement of Young Children's Engagement and Problem Behavior in Early Childhood Settings. (November 2018) - Prykanowski, Debra A.; Martinez, Jose R.; Reichow, Brian; Conroy, Maureen A.; Huang, Ke
Given the importance of engagement and impact of problem behavior on young children's behavioral, social, and academic development, these two behaviors are often observed and measured in early childhood settings. The purpose of this brief report is to describe the findings from an examination of the use of multiple direct observation methods to measure engagement and problem behaviors of five children in early childhood settings across two different activity types. Findings from this study support previous research that young children's engagement and problem behavior differ depending on the type of classroom activity. In addition, the data indicate that behavioral estimates for both engagement and problem behavior obtained using momentary time sampling produced measures of behaviors comparable with those obtained with continuous recording, whereas partial-interval recording consistently overestimated the occurrence of the behaviors compared with continuous recording. Implications of the findings and directions for future research are discussed.